THE CORRELATION BETWEEN STRATEGIC PLANNING AND ECONOMIC MOROCCAN SME’s PERFORMANCE - Hassan ABBAR; Salma ECHCHARQY (Management & Marketing, 2016)
Among management activities, the strategic function retains increasingly attention of authors being interested in SME's (small and medium-sized enterprise) performance. Indeed, there are many authors who think that by following a strategy building formal process, SMEs can increase chances of success, while others consider that by trusting their manager’s intuition, SMEs can stimulate creativity and develop important competitive advantages at the same time. Further to these controversies, we aim through this communication to partake in this debate mattering to both researchers and managers by revising the relation between strategic planning and SMEs' economic performance. So as to handle this matter, we verify nearby 100 Moroccan SMEs, the degree of importance they grant to strategic planning. We also examine how SMEs strategic planning may or not be associated with their economic performance as measured by average variation sales over the last three years.